Application of the Fuzzy Optimal Model in the Selection of the Startup Hub. (4th February 2021) - Zhu, Xinman; Dai, Jie; Wei, Haoran; Yang, Debing; Huang, Weilun; Yu, Zhang
Abstract : This paper integrates nominal group technique (NGT), analytical hierarchy process (AHP), and fuzzy technique for order preference by similarity to an ideal solution (TOPSIS) approach, and a case study has been used to demonstrate the fuzzy optimal selection model. From a literature review on the startup hub and the interviews conducted with officials and experts, the selection criteria are (1) convenience—promoted by the city's entrepreneurial policies or its traffic infrastructure; (2) potentiality—promoted by a regional network or value chain of startups. Lastly, the best idle land resulted in this case study with equal decision-making power using the fuzzy method is Taipei Jianguo Brewery, and the difference of decision-making power might make the best idle land to be Wanbao Textile Factory.